The Impact of Common Epidemiological Factors on Gray and White Matter Volumes in Magnetic Resonance Imaging–Is Prevention of Brain Degeneration Possible? - Jacków-Nowicka, Jagoda; Podgórski, Przemysław; Bladowska, Joanna; Szcześniak, Dorota; Rymaszewska, Joanna; Zatońska, Katarzyna; Połtyn-Zaradna, Katarzyna; Szuba, Andrzej; Sa̧siadek, Marek; Zimny, Anna (Frontiers in Neurology, 2021)
Introduction: The aim of the study was to evaluate the impact of multiple risk factors (age, diabetes, hypertension, hyperlipidemia, BMI, smoking, alcohol) on the gray and white matter volumes as well as on the burden of white matter hyperintensities (WMH). Material and Methods: The study group consisted of 554 subjects (age range: 50–69 yrs, F/M: 367/187) recruited from the larger cohort of the Polish fraction of the Prospective Urban Rural Epidemiological (PURE) study. The participants answered questionnaires about their lifestyle, underwent physical and psychological examination (MoCA test), laboratory blood tests followed by brain MRI. Volumetric measurements of the total gray matter (GMvol), total white matter (WMvol) and WHM (WMHvol) normalized to the total intracranial volume were performed using the Computational Anatomy Toolbox 12 (CAT12) and Statistical Parametric Maps 12 (SPM12) based on 3D T1-weighted sequence. The influence of risk factors was assessed using multiple regression analysis before and after correction for multiple comparisons. Results: Older age was associated with lower GMvol and WMvol, and higher WMHvol (p < 0.001). Smaller GMvol volume was associated with higher WMHvol (p < 0.001). Higher WMHvol was associated with hypertension (p = 0.01) and less significantly with hyperlipidemia (only before correction p = 0.03). Diabetes, abnormal BMI, smoking and alcohol intake did not have any significant impact on GMvol, WMvol or WMHvol (p > 0.05). MoCA score was not influenced by any of the factors. Conclusions: Gray matter loss is strongly associated with the accumulation of WMH which seems to be potentially preventable by maintaining normal blood pressure and cholesterol levels.